2015
DOI: 10.1016/j.jadohealth.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of School Subsidies on HIV-Related Outcomes Among Adolescent Female Orphans

Abstract: Objectives We examine effects of school support as a structural HIV prevention intervention for adolescent female orphans in Zimbabwe after 5 years. Methods 328 orphan adolescent girls were followed in a clustered randomized control trial from 2007 to 2010. The experimental group received school fees, uniforms, and school supplies and were assigned a school-based “helper.” In 2011-12, the control group received delayed partial treatment of school fees only. At the final data point in 2012, survey, HIV, and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
90
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(93 citation statements)
references
References 28 publications
3
90
0
Order By: Relevance
“…Cultural norms to marry by a certain age may override a girl taking advantage of the opportunity to stay in school. From our study experience, we found that rural girls, particularly those who do not have school fees, are increasingly likely to drop out and marry as they get older (Hallfors et al, 2015). From other analyses, we found that Apostolic religious affiliation was strongly associated with greater likelihood of early marriage and school dropout among rural orphan girls (Hallfors et al, 2013).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Cultural norms to marry by a certain age may override a girl taking advantage of the opportunity to stay in school. From our study experience, we found that rural girls, particularly those who do not have school fees, are increasingly likely to drop out and marry as they get older (Hallfors et al, 2015). From other analyses, we found that Apostolic religious affiliation was strongly associated with greater likelihood of early marriage and school dropout among rural orphan girls (Hallfors et al, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…In 2012, the conditional dropout rate increased further to 17.3% in the control/delayed partial intervention group, and to 12.8% in the intervention. Participants were then, on average, almost 17 years old and marriage rates were rising particularly among the control/delayed partial intervention group (Hallfors et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations